CT Brain Findings in COVID-19 Patients with Neurological Symptoms: A Descriptive Study from a Tertiary Care Hospital in Pakistan - Aman, Nasreen; Aziz, Rukhsana (Journal of Rawalpindi Medical College, 2025)
Objectives: This study aimed to explore the spectrum of CT brain findings in COVID-19 patients presenting with neurological symptoms and to evaluate their association with age and underlying comorbidities. Methods: A retrospective review was conducted on 60 RT-PCR–confirmed COVID-19 patients who underwent CT brain at Lady Reading Hospital, Peshawar, from March to November 2021 due to neurological complaints such as altered mental status, headache, seizures, or focal deficits. Patient data, including demographics, comorbid conditions, and imaging findings, were collected. Data was analysed using descriptive and inferential statistics. Results: The most frequent abnormality observed was ischemic infarction, present in 40% of patients, with a clear predominance among elderly individuals and those with comorbidities such as hypertension and diabetes mellitus. Brain atrophy was identified in 11.7% of cases, while intracranial haemorrhage was noted in 10%. Other, less common findings included hypoxic changes and nonspecific white matter abnormalities. Statistical testing revealed significant associations between age groups, comorbidity status, and occurrence of ischemic or hemorrhagic events (p < 0.05). Conclusion: CT brain imaging in COVID-19 patients with neurological manifestations demonstrated a high frequency of structural abnormalities, particularly vascular insults. These findings suggest that SARS-CoV-2 infection may exacerbate cerebrovascular vulnerability in older and comorbid populations. Early neuroimaging in such patients is crucial for timely diagnosis and management. Further large-scale prospective studies are warranted to validate these associations and to guide neuroimaging protocols in severe COVID-19. Keywords: COVID-19, Computed Tomography of Brain, Neurologic Manifestations, Cerebral Infarction, Hypertension